Response of Salivary Markers of Autonomic Activity to Elite Competition - Diaz, M. M.; Bocanegra, O. L.; Teixeira, R. R.; Soares, S. S.; Espindola, F. S. (International Journal of Sports Medicine, 2012)
We investigated the response of salivary total protein (TP), alpha-amylase (sAA) and chromogranin A (CgA) to sporting competition and their relation with positive and negative affect. 11 professional swimmers were examined during the first day of a national contest and on a recreated event that matched time-of-the-day and day-of-the-week assessments 2 weeks later. Total protein was determined by the Bradford method and sAA and CgA by Western blotting upon awakening, 30 and 60 min post awakening, immediately before warming up for competition and 5, 20 and 60 min after competition. Psychometric instruments included the Positive Affect and Negative Affect Schedule-X. The concentrations of TP, sAA and CgA differed from controls only prior to and 5 min after the event. We observed positive correlations between higher negative affect scores with higher levels of TP, sAA and CgA prior to the event on the competition day. All 3 markers showed a similar reactivity to sporting competition, which may be attributed to the mechanisms responsible for protein secretion into saliva when collection is performed with no exogenous stimulation. TP is an attractive marker in sports psychology since its determination is faster and cheaper than traditional kinetic or immune assays.
Keywords: saliva; exercise; stress; biomarker